The content of life values and orientations of deviant teenagers - Babyi, Mukola (Psychological Prospects Journal, 2015)
Adolescence is characterized by scientists as the transition from childhood to adulthood. This period is characterized by reassessment of life values and orientations. The process involves macro- and microenvironment, the institutions of socialization and society. Their contents and the transformation of the child to the adult are dependent on specificity of life values and orientations, namely of social or antisocial type.Teens face a dilemma, and therefore seek support in determining the basic life orientations of the adult world from close friends who have the same problems. When life orientations of the nearest influential environment are formed and developed in the line of antisocial behavior the emergence of deviant ongoing can be predicted with a high probability.Thorougly examined the levels of life orientations and values of deviant ado–lescents, we found that the most distinct and developed are individualistic values (consumption values) corresponding to the first stage of human consciousness development – egocentrism that characterizes the child who requires attention of others, care, love without mutual response. The most actual to this teenager is the position: «Me», «For me», «I am on my own».
Keywords: adolescence, life values and orientations, microenvironment, socialization